Fibroblast growth factor signaling in embryonic and cancer stem cells - Dvořák, Petr; Dvořáková, Dana; Hampl, Aleš (FEBS letters, 2006)
Cancer stem cells are cancer cells that originate from the transformation of normal stem cells. The most important property of any stem cell is the ability to self-renew. Through this property, there are striking parallels between normal stem cells and cancer stem cells. Both cell types share various markers of "stemness". In particular, normal stem cells and cancer stem cells utilize similar molecular mechanisms to drive self-renewal, and similar signaling pathways may induce their differentiation. The fibroblast growth factor 2 (FGF-2) pathway is one of the most significant regulators of human embryonic stem cell (hESC) self-renewal and cancer cell tumorigenesis. Here we summarize recent data on the effects of FGF-2 and its receptors on hESCs and leukemic stem/progenitor cells. Also, we discuss the similarities of these findings with stem cell renewal and differentiation phenotypes.
Keywords: hematologické nádory; kultivované buňky; Humans; Hematologic Neoplasms; kmenové buňky; signální transdukce; Cells, Cultured; Stem Cells; fibroblastové růstové faktory; embryo savčí; Financing, Organized; financování organizované; lidé; Fibroblast Growth Factors; Embryo, Mammalian; Signal Transduction